Functionalization of α-synuclein fibrils - Povilonienė, Simona; Časaitė, Vida; Bukauskas, Virginijus; Šetkus, Arūnas; Staniulis, Juozas; Meškys, Rolandas (Beilstein Journal of Nanotechnology, 2015)
The propensity of peptides and proteins to form self-assembled structures has very promising applications in the development of novel nanomaterials. Under certain conditions, amyloid protein α-synuclein forms well-ordered structures – fibrils, which have proven to be valuable building blocks for bionanotechnological approaches. Herein we demonstrate the functionalization of fibrils formed by a mutant α-synuclein that contains an additional cysteine residue. The fibrils have been biotinylated via thiol groups and subsequently joined with neutravidin-conjugated gold nanoparticles. Atomic force microscopy and transmission electron microscopy confirmed the expected structure – nanoladders. The ability of fibrils (and of the additional components) to assemble into such complex structures offers new opportunities for fabricating novel hybrid materials or devices.
Keywords: α-synuclein; atomic force microscopy; gold nanoparticles; nanostructures; self-assembly